PENGARUH MODEL PEMBELAJARAN DISKUSI TERBIMBING TERHADAP PENGEMBANGAN KETERAMPILAN BERPIKIR ABAD 21 DI SMKN PERTANIAN TERPADU PROV. RIAU - Herma Liza; Gimin; Haryono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by problems in the learning process, namely students do not follow carefully when the teacher is explaining, students have difficulty in answering questions asked by the teacher. Low ability of 21st Century Thinking Skills, Lack of variation in learning methods used by teachers, and lack of student involvement in the learning process. Therefore, a guided discussion learning model is applied as an effort to improve students' 21st century thinking skills. The formulation of the problem in this study is whether there is an influence of the Influence of the Guided Discussion Learning Model on the Development of 21st Century Thinking Skills at Integrated Agricultural Vocational Schools in Riau Province. The purpose of this study is to determine the Influence of the Guided Discussion Learning Model on the Development of 21st Century Thinking Skills. This study is expected to provide scientific contributions in the field of education and become a theoretical basis for the development of PPKn learning. This study is a type of quantitative experiment with a one-group Pretest Posttest Design. The population in this study were grade X students. Sample data collection in this study was carried out by purposive sampling, as many as 1 class totaling 27 students. The results of the data analysis show that there is an influence and significance between the guided discussion learning model and students' 21st century thinking skills. The significance value (Sig.) Based on the mean is 0.853> 0.05. (2-tailed) of 0.001 <0.05. Thus, the Ha hypothesis is accepted. In conclusion, the Guided Discussion Learning Model is quite effective in improving the Development of 21st Century Thinking Skills of students at the Integrated Agricultural Vocational High School of Riau Province.